Improving the POSPAY Mobile Interface Using User-Centered Approach with User Experience Questionnaire Evaluation - Tasya Arnomel Mareta; Evi Yulianingsih; Ari Muzakir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Digital public service applications require interfaces that are clear, efficient, and consistent to support fast and accurate transactions. In the PT Pos Indonesia service environment, POSPAY users may experience difficulties in locating core services, understanding menu structures, and completing tasks efficiently due to navigation and interface consistency issues. This study aims to improve the POSPAY mobile interface using a user-centered approach and to evaluate user experience using the User Experience Questionnaire. The study involved 20 participants (staff and customers). Observation and semi-structured interviews were conducted to elicit user needs, which were translated into prioritized requirements and implemented in a high-fidelity clickable prototype developed with Figma. Participants completed standardized task scenarios before completing the questionnaire. The results show positive mean scores in five dimensions, with Perspicuity (1.70) and Efficiency (1.55) as the highest, followed by Attractiveness (1.45), Dependability (1.20), and Stimulation (1.05). Novelty (0.65) remained neutral, indicating that the proposed interface is perceived as functional but not strongly innovative. The main contribution of this study is a context-specific requirement set and traceable mapping between user needs and prototype features for POSPAY in a postal service setting, supported by quantitative user experience evidence to prioritize interface refinement and implementation decisions at PT Pos Indonesia.